Designing gamification application based on user type - Ryan Macdonell Andrias; Jetol Bolongkikit (Pusat e-pembelajaran, UMS, 2021)
The use of game design elements in non-game contexts is referred to as gamification. It is worth noting that each user's preference for a game mechanic and game element is unique. It is common practice to include multiple game elements to accommodate all user/player types to meet user expectations. However, this approach may cause the user interface to become congested with irrelevant game elements. This study suggests designing adaptive gamification with proper mapping of user types and game elements. A total of 915 questionnaires (HEXAD user type) from Universiti Malaysia Sabah undergraduate students were evaluated. The PLS-SEM method was used to analyse the data in the current study, which was accomplished through the use of the SmartPLS software. According to the user type analysis, the gamification designer should prioritise socialiser game elements, followed by philanthropist and player type. The entire gamification system should be designed so that it adapts to the unique requirements of each user.